Les groupements d'intérêt économique - Guyon, Yves (Les Cahiers de droit, 1981)
Collaboration between different business enterprises has become a must in our days of financial, technical and commercial complexity. It is highly encouraged by governments and businessmen. The traditional legal techniques known and frequently used in Canada appear however to be inadequate in some cases. The French legislator has innovated in the field by creating, in 1967, the legal framework of the Groupement d'intérêt économique (G.I.E.) The G.I.E. is an institution that has the separate legal entity of the corporation while maintaining the joint, several and illimited liability of the partners. The G.I.E. is all the way neutral. It is not aimed to generate direct profits for itself or the partners but allows the involved partners to have a better overall performance. Since 1967, over 9000 G.I.E. have been created in France to cover fields as different as the Airbus joint venture, communal maintenance services, research publicity or marketing department, buying or export offices, etc. This article, written by a leading academic, discusses the different legal aspect of the G.I.E. and explains the pros and cons of the institution.